2021
DOI: 10.1007/s00348-021-03218-3
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds stress tensor measurements using magnetic resonance velocimetry: expansion of the dynamic measurement range and analysis of systematic measurement errors

Abstract: This study presents magnetic resonance velocimetry (MRV) Reynolds Stress measurements in a periodic hill channel with a hill Reynolds number of Re = 29,500. The velocity encoding scheme is based on the ICOSA6 method with six icosahedral encoding directions and multiple encoding values are measured to increase the dynamic range. The full Reynolds stress tensor is obtained from a voxel-wise three-dimensional Gaussian fit using the magnitude data of all acquisitions. The MRV results are compared to a wall-resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…A previous MRI study demonstrated that significant error in the velocity variance is introduced by incorrectly assuming the form of the velocity distribution function. 33 Because the flow characteristics of the Schwarz Diamond geometry are unclear, we assume that the velocity fluctuations are normally distributed with a variance of u 2 for simplicity. Therefore, integrating with respect to u and normalizing by the signal at p = 0, which is defined by S 0 , gives the signal in terms of the velocity distribution parameters:…”
Section: Mr Velocity Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous MRI study demonstrated that significant error in the velocity variance is introduced by incorrectly assuming the form of the velocity distribution function. 33 Because the flow characteristics of the Schwarz Diamond geometry are unclear, we assume that the velocity fluctuations are normally distributed with a variance of u 2 for simplicity. Therefore, integrating with respect to u and normalizing by the signal at p = 0, which is defined by S 0 , gives the signal in terms of the velocity distribution parameters:…”
Section: Mr Velocity Imagingmentioning
confidence: 99%
“…A previous MRI study demonstrated that significant error in the velocity variance is introduced by incorrectly assuming the form of the velocity distribution function 33 . Because the flow characteristics of the Schwarz Diamond geometry are unclear, we assume that the velocity fluctuations are normally distributed with a variance of ⟨⟩u2 for simplicity.…”
Section: Theorymentioning
confidence: 99%